Customer Knowledge Management Success Factors and Challenges in Service-Related Sectors: A Systematic Literature Review - Nurul Aulia Larasati; Monica Ratna Andani; Nadya Safitri; Dana Indra Sensuse (Eduvest - Journal of Universal Studies, 2025)
Customer Knowledge Management (CKM) has become crucial for organizations in service-related sectors aiming to enhance customer satisfaction, loyalty, and overall performance through effective management of knowledge for, from, and regarding customers. However, implementing CKM presents both opportunities and significant hurdles. The purpose of this study is to provide an exhaustive understanding of these aspects by systematically reviewing recent literature to identify the critical success factors and key challenges associated with CKM implementation in service-related sectors. A systematic literature review (SLR) was conducted following established guidelines, searching major academic databases (Scopus, IEEE Xplore, ACM Digital Library, Taylor & Francis, ScienceDirect) for relevant studies published up to 2025. Following a rigorous screening and quality assessment process, 21 primary studies were selected for data extraction and synthesis. The findings reveal several key success factors categorized under Technology (e.g., CRM platforms, collaborative tools), Organization (e.g., top management support, customer-oriented culture, clear strategy), Human (e.g., employee skills, training, trust), and CKM Process (e.g., effective knowledge acquisition, sharing, application). Conversely, significant challenges identified include strategic issues (e.g., lack of clear objectives, difficulty measuring value), technological barriers (e.g., lack of appropriate technology, data integration issues), organizational and cultural resistance (e.g., lack of sharing culture), and human resource challenges (e.g., skill gaps, high turnover, knowledge hiding). This review consolidates current knowledge, offering valuable insights for practitioners seeking to navigate CKM implementation in service industries and providing directions for future research.